Food neophobia and its association with dietary choices and willingness to eat insects - Hopkins, Indee; Farahnaky, Asgar; Gill, Harsharn; Danaher, Jessica; Newman, Lisa P. (Frontiers in Nutrition, 2023)
Growing populations, changing dietary preferences and limitations on natural resources have meant that finding an alternative to traditional animal-based protein sources is a priority. Insects have been proposed as a possible solution due to their many benefits including low resource inputs and rich nutritional profile. However, insects are not consumed on a large scale by Australians. Food neophobia (reluctance to try new foods) could be contributing to this delay and as such, this study aimed to explore the role of food neophobia on protein food source habits and willingness to eat insects as food. A total of 601 participants (76.2% female, 23.8% male) completed an online survey which included a questionnaire measuring food neophobia status, participants’ self-reported usual protein dietary habits, their previous insect-eating experience, future willingness to eat insects, and potential motivations to include insects in their diet. Results indicated a strong association between food neophobia and participants' dietary choices such as following a vegan or vegetarian diet (p=0.024). In addition, food neophobia was correlated with a reduced likelihood of previous insect-eating experience (p<0.001), as well as a decreased willingness to eat insects in the future (p<0.001). This study provides a greater understanding of the role of food neophobia status and dietary choices in consumers’ willingness to eat insects and identifies possible motivating factors that may increase the likelihood of consumers’ future insect eating.